2018
DOI: 10.3390/pharmacy6030096
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Quality of Medicines in Yangon, Myanmar

Abstract: Many poor-quality medicines are supplied to patients mainly in developing countries. No systematic survey on counterfeit medicines has been conducted in Myanmar since 1999. The purpose of this study was to investigate the current situation of substandard or counterfeit medicines in Myanmar. Samples of oral medicines, cefuroxime axetil (CXM), donepezil hydrochloride (DN) and omeprazole (OM), and injections, ceftriaxone sodium (CTRX), and gentamicin sulfate (GM), were collected from pharmacies, hospitals, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Sampling was carried out in Mandalay, the second most populous city of Myanmar after Yangon with a population of nearly 1.2 million; it is the major trading and communications center for northern and central Myanmar. We selected this city after the 2013' investigation in Yangon [9]. The sampling sites were private hospitals, clinical pharmacies, community pharmacies and wholesalers in Chan-Aye-Thar-San Township, Pyi-Gyi-Tagon Township, Aung-Myay-Thar-San Township, Mahar-Aung-Myay Township of Mandalay District, Pyin-Oo-Lwin Township of Pyin-Oo-Lwin District, and Mite-Htee-Lar Township of Mite-Htee-Lar District in the Mandalay region.…”
Section: Sampling Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…Sampling was carried out in Mandalay, the second most populous city of Myanmar after Yangon with a population of nearly 1.2 million; it is the major trading and communications center for northern and central Myanmar. We selected this city after the 2013' investigation in Yangon [9]. The sampling sites were private hospitals, clinical pharmacies, community pharmacies and wholesalers in Chan-Aye-Thar-San Township, Pyi-Gyi-Tagon Township, Aung-Myay-Thar-San Township, Mahar-Aung-Myay Township of Mandalay District, Pyin-Oo-Lwin Township of Pyin-Oo-Lwin District, and Mite-Htee-Lar Township of Mite-Htee-Lar District in the Mandalay region.…”
Section: Sampling Areasmentioning
confidence: 99%
“…Further, there were sporadic reports concerning Myanmar in 2001 and 2008 [7,8]. Therefore, we started a survey in Myanmar in 2014 [9,10], and followed that with the present in 2015. Because the number of patients with long-term diseases in developing countries is increasing [11], not only on anti-microbials, but also on medicines against chronic or life-style related diseases are important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of some established medicines have shown that the incidence of substandard products in Cambodia has declined in recent years, which can be attributed to the strong action of the government of Cambodia, with international cooperation. 25 However, substandard and falsified medicines remain on sale in Cambodia, 26,27 and the status of antimicrobials as well as other essential medicines for communicable and NCDs remains to be fully investigated. 27,28 Therefore, the aim of this project was to investigate the status of selected medicines for NCDs in the private market in Cambodia, to provide data for guiding further actions and countermeasures to reduce the prevalence of SFs among these medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the global efforts and directive regulations against SF medical products, local laboratories also need efficient analytical methods to survey the (illegal) drug market. The majority of papers related to SF antimicrobials deal with the determination of APIs using liquid chromatography‐ultra violet (LC−UV) and/or liquid chromatography−mass spectrometry (LC–MS) . However, other parameters may also have a tremendous influence on drug efficacy and toxicity.…”
Section: Introductionmentioning
confidence: 99%